2017
DOI: 10.1007/s41669-017-0057-9
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Pocket Expenditures, Indirect Costs and Health-Related Quality of Life of Patients with Pulmonary Tuberculosis in Thailand

Abstract: BackgroundThailand’s hospitals may adopt different supervision approaches to improve tuberculosis (TB) treatment adherence.ObjectiveThe aim of this study was to compare out-of-pocket (OOP) expenditures, indirect costs, and health-related quality of life (HRQoL) among TB patients who received pharmaceutical care (pharmacist-led patient education and telephone consultation), home visit, and self-administered therapy (SAT) in Thailand.MethodsWe conducted a prospective study to collect OOP expenditures, indirect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Compared with illiterate patients, the economic costs of patients in junior high school were higher. When patients receive only junior middle school education, they will be more aware of seeing a doctor and pay more attention to health than illiterate patients [ 45 ]. However, compared with patients with higher education, patients with junior middle school education may not better understand hospital procedures and medical knowledge [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with illiterate patients, the economic costs of patients in junior high school were higher. When patients receive only junior middle school education, they will be more aware of seeing a doctor and pay more attention to health than illiterate patients [ 45 ]. However, compared with patients with higher education, patients with junior middle school education may not better understand hospital procedures and medical knowledge [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The indirect costs could be due to absenteeism from work and loss of productivity and income while suffering because of long course of disease and recovery pathway. Among Thai adults, a study reported that patients experienced highest indirect costs out of total expenditure due to the patients’ reduced ability to work and loss of income [ 24 ]. The policy implication to curb the higher indirect costs and loss of income might be an assistance of TB patients with leave compensation with introducing a paid sick leave package along with the flexibility in working hours.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies originated from high-TB-burden countries, including four from India (Bhardwaja et al, 2012;Venkatapraveen et al, 2012;Thomas et al, 2018;Narayana et al, 2020), one from China (Tang et al, 2018), and one from Indonesia (Karuniawati et al, 2019). Others were from different regions: Thailand (Tanvejsilp et al, 2018), Ivory Coast (Abrogoua et al, 2016), Türkiye (Clark et al, 2007), andBrazil (Lopes et al, 2017). The earliest included study was published in 2007.…”
Section: Study Selectionmentioning
confidence: 99%
“…Notably, among the 10 studies, no randomized controlled studies were identified. Study designs were heterogeneous and included five prospective cohort studies (50%) (Bhardwaja et al, 2012;Venkatapraveen et al, 2012;Lopes et al, 2017;Tanvejsilp et al, 2018;Thomas et al, 2018), two case-control studies (20%) (Clark et al, 2007;Tang et al, 2018), two quasi-experimental studies (with and without control) (Karuniawati et al, 2019;Narayana et al, 2020), and a cross-sectional study (Abrogoua et al, 2016). Most studies were prospective; for only one study, this was unknown (Abrogoua et al, 2016).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation